Evaluation of an Indirect ELISA Using Recombinant Arginine Kinase for Serodiagnosis of Psoroptes ovis var. cuniculi Infestation in Rabbits - Gu, Xiaobin; Gu, Jiang; Ren, Yongjun; Zheng, Youle; Yang, Guangyou; Zhou, Xuan; Xie, Yue (Frontiers in Veterinary Science, 2019)
Psoroptes ovis var. cuniculi is a common ectoparasite of the wild and domestic rabbits worldwide, which causes significant economic losses in commercial rabbit breeding. In China, the diagnosis of rabbits infested with P. ovis var. cuniculi currently relies on detection of clinical signs and Psoroptes mites in skin scrapings by microscopy examination. However, this method is not very efficient in detection of the low mite loads and/or sub-clinical infections. In the present study, we cloned and expressed an arginine kinase homologue gene from P. ovis var. cuniculi (Poc-AK) and used its recombinant protein rPoc-AK to develop an indirect enzyme-linked immunosorbent assay (iELISA) method for diagnosis of P. ovis var. cuniculi infestation in rabbits. The results showed that the rPoc-AK protein was ~ 61 kDa and had no signal peptide. The rPoc-AK-based iELISA achieved a 94.4% sensitivity and a 88.2% specificity, and was able to detect P. ovis var. cuniculi infection as early as the 1st week post-infection, prior to the appearance of clinical signs. Further field study showed 24.94% (66.3/266) clinically normal rabbits were seropositive with the highest and lowest seropositive rates for California (35.71%) and Belgian (15.14%), respectively. These results suggested that the rPoc-AK has potential as a diagnostic antigen for early P. ovis var. cuniculi infestation in rabbits.